Upaya guru tahfizh dalam meningkatkan kemampuan menghafal al-Qur’an siswa MIT Isykarima Karanganyar - Abdur Rahman; Nurul Latifatul Inayati (At Turots: Jurnal Pendidikan Islam, 2023)
Memorizing the Qur'an is an activity that can be done by everyone to maintain the purity of the Qur'an. Lucky for those who can protect the Qur'an, memorize and also practice it. It is very clear that memorizing the Qur'an is not an easy thing, it takes special time, sincerity and seriousness. For this reason, the Qur'an must be introduced to children from an early age as a guide to navigate their lives later, because children are the assets of the nation's next generation who will defend their religion and nation. The role of the teacher is no less important, the teacher has a great influence on teaching and motivating memorization and providing methods that make it easier for a child to love and not get bored memorizing it. Based on the above unrest, the author is interested in conducting research related to how the tahfidz teacher's efforts in improving students' memorization skills and to find out the obstacles faced by asatidz in an effort to improve the ability to memorize the Qur'an of students. Therefore, the research is entitled "Tahfidz Teacher's Efforts in Improving the Ability to Memorize Al-Qur'an Santri MIT Isykarima Karanganyar".The research method that the author uses is a qualitative method with the type of field research because researchers want to know more about the problems that exist at MIT Isy Karima. The results of this study are: MIT Isy Karima in teaching the Koran students use the QIWAKI program, TAWAMUR and supporting programs. teacher efforts in teaching tahfizh students using the talqin method. The solution to the existing obstacles is to inform the student's guardian about the tahfizh program at MIT Isy Karima and provide more time for students who have less ability.